Implementation of Project-based Learning Method to Enhance Numeracy Ability of Procedural Text Material of English Subject - Pratiwi, Margarett Henni; Herlinawati, Herlinawati (Lectura : Jurnal Pendidikan, 2025)
The National Examination (Ujian Nasional/UN) has been replaced by the National Assessment (Asesmen Nasional/AN), which includes the Minimum Competency Assessment (Asesmen Kompetensi Minimum/AKM), a character survey, and an assessment of the learning environment. The basis of this research lies in the observation that numerous teachers still employ a monotonous teaching style, leading to students feeling sleepy during the learning process due to the teacher’s ineffective methods. Consequently, the mastery of the material remains low, resulting in decreased student achievement. The aim of this research is to enhance the engagement of students and the professionalism of teachers during the English teaching and learning process, thereby improving the quality of student learning outcomes. To achieve this aim, classroom action research was undertaken over two cycles. In the pre-cycle, the author delivered material using an individual work approach, yielding a result of only 20.58% in the complete category. In cycle I, students achieved a result of 38.24% in the complete category. Similarly, in cycle II, the results rose to 94.11% in the complete category. From the comparison of results from pre-cycle to cycle II, it can be concluded that the Project-based Learning methods effectively enhance the numeracy skills of students in English lessons. The findings of this study strongly suggest that the Project-based Learning method is a valuable pedagogical approach for enhancing numeracy skills within the English language classroom.